RESISTANCE LEVEL OF SOME SOYBEAN (Glycine max L. Merr) GENOTYPES TOWARD SALINITY STRESS - Runik Dyah Purwaningrahayu; Husni Thamrin Sebayang; Syekhfani Syekhfani; Nurul Aini (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2015)
Salinity resistance level on soybean which influenced by its genotype is important to be explored.One of the important factors which determine the success of soybean cultivation on saline soil or salt-affected soil is salinity resistance level. Eleven variants or genotypes of soybean were collected from Indonesian Legumes and Tuber Crops Research Institute and were tested on four different electrical conductivity level of soil (0.5 dS/; 5.8 dS/m; 8.4 dS/m; and 12.2 dS/m). Soybeans were planted on pot in green house. Salinity stress will started when plants were on 21 days after planting (DAP). The treatment was watering using some different concentration of sea water for 30 days. Three methodswhich used to determine salinity resistance level of soybean were seed yield reduction level, stress susceptibility index (SSI), and leaf scorch score. Soybean will classified into salinity tolerant genotype group when weight reduction of seed was <66%, leaf scorch score was <2.0 and SSI was <0.95. Results showed that genotypes with 0.5-5.8 dS/mof soil electrical conductivity tolerance were: Wilis, Tanggamus, Gema, LK/3474-403, MLG 3474-991, IAC100/Burangrang//Malabar-10-KP-30-75, MLG 2805-962; genotypes with8.4 dS/m of soil electrical conductivity tolerance were SU-7-1014 and Argomulyo//IAC100-10-KP-40-120; and genotypes with 12.2 dS/m of soil electrical conductivity tolerance were IAC100/Burangrang//Malabar-10-KP-21-50 and Argopuro//IAC100. These results can be used by soybean breeder as a reference in improving salinity resistance level of soybean for further study as anticipation of salt affected soil wide spread.